Feasibility and acceptability of a virtual learning module for navigating angry conversations in clinical encounters - Valerie Shilling; Rachel Starkings; Lesley Fallowfield (BMC Medical Education)
Abstract Background The use of technology in medical education has been increasing with more students exposed to some form of online learning or tutorials, under the umbrella of virtual learning (VL). Many programmes, particularly those involving virtual reality, have centred on practical skills, such as surgical techniques or anatomical knowledge, rather than communication. The study presented here examined the feasibility and acceptability of a VL module developed to aid communication when handling angry patients and their relatives. Methods Participants were 4th and 5th year medical students at the Brighton and Sussex Medical School. Students were randomly allocated to receive training about having angry conversations in a clinical setting via virtual reality headset or desktop application. Prior to the intervention, everyone completed the SE12 self-efficacy questionnaire, a 5-item confidence measure, and free-response study specific survey. Following the module, they completed another study specific survey, with fixed and free responses, the confidence measure, along with the UTAUT2 questionnaire on acceptance and use of technology. Quantitative data was analysed descriptively, conceptual content analysis was applied to free responses. Participants received a £25 voucher for their time. Results Twenty students took part in the project. Scores on the SE12 did not differ significantly between intervention arms. Confidence improved across all five categories - recognising responses that diffuse or exacerbate anger, identifying anger signals, remaining calm in hostile situations, moving forward with empathy, and applying techniques to different situations. Responses to the UTAUT2 indicated acceptance of VL, including the psychological safety it provides. Nineteen categories for free text responses were developed via content analysis. Participants spoke frequently about the challenges of navigating anger. There was initial apprehension VL would not feel realistic, though this was largely reversed post-intervention. Students expressed preference for a combination of VL, whichever modality, and face-to-face teaching, recognising benefits of both. Conclusion Students found the training to be acceptable, providing them with tangible skills. There should be a consideration as to how to incorporate VL, with a mix of face-to-face practice for added realism. Trial Registration Clinical trial number not applicable.